Prevalence of Leg Ulcers in Sickle Cell Disease and Their Association with Disease Severity, Inflammatory, and Oxidative Stress Markers: Prevalence of Leg Ulcers in Sickle Cell Disease and Oxidative Stress Markers - Jawaid, Muhammad Tauseef; Memon, Faiza; Shafi, Rubina; Azhar, Sarah; Faiz, Faiz Ahmed; Khan, Rana Muhammad Asad (Pakistan Journal of Health Sciences, 2025)
Leg ulcers are a devastating problem of sickle cell disease (SCD) and are associated with elevated inflammation and oxidative stress. Understanding their prevalence, severity, and biochemical associations is essential for improved management. Objective: To determine the prevalence and severity of leg ulcers in sickle cell disease and evaluate their association with oxidative and inflammatory stress markers, addressing the gap in the literature regarding biochemical correlates of ulcer development in SCD patients. Methods: This cross-sectional study was carried out at Gujranwala Teaching Hospital, Gujranwala Medical College. A total of 323 genetically confirmed SCD patients were enrolled. Clinical data, including leg ulcer characteristics and SCD severity, were documented. Serum levels of Tumor Necrosis Factor Alpha (TNF-α), Interleukin-6 (IL-6), Total Antioxidant Capacity (TAC), and Total Oxidative Stress (TOS) were quantified using ELISA. Statistical analysis was completed using SPSS-25. Results: The prevalence of leg ulcers was 30.0% (97/323; 95% CI: 25.1%–35.3%), increasing with SCD severity (p<0.001). Ulcerated patients had significantly higher TNF-α (28.5 ± 5.3 vs. 19.6 ± 4.8 pg/mL; 95% CI for difference: 7.3–10.2, p<0.001) and IL-6 (21.2 ± 4.7 vs. 12.9 ± 3.6 pg/mL; 95% CI: 6.9–9.6, p<0.001). TOS was elevated (48.7 ± 9.5 vs. 32.3 ± 7.1 µmol H₂O₂ equiv./L; 95% CI: 13.5–18.2, p<0.001), while TAC was lower (0.82 ± 0.14 vs. 1.27 ± 0.21 mmol Trolox equiv./L; 95% CI: –0.54 to –0.38, p<0.001). Conclusions: Leg ulcers are prevalent in SCD, particularly in patients with severe disease. SCD severity showed significant associations with inflammatory and oxidative stress markers.